ISLAMIC ETHICS IN COMMUNICATION CROSS POLITICAL PARTIES - Saeful Rokhman (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
To find out Islamic ethics in communicating across political parties. Research method: Qualitative. Research Results: Every time we welcome the General Election and the Presidential Election, disputes occur so fiercely, both in the real world and in cyberspace. Swearing and swearing in order to defend the party and its lord became our daily food. Therefore, we need to apply three Islamic ethics in communicating across political parties, namely politics without hoaxes, politics without cheating, and politics without criticizing.